Twenty years of lion conservation in a commercial rangeland - Frank, Laurence G. (Frontiers in Ecology and Evolution, 2023)
Lion populations in Africa declined precipitously in the twentieth century outside of protected areas but the commercial cattle ranches of Laikipia County, Kenya, have been a unique exception, with low livestock stocking rates, careful range management, large populations of wild ungulates, and a full complement of large carnivores, including lions at a stable density of about 6/100 km2. The Laikipia Predator Project, later Living With Lions, started in 1997 with two primary objectives: improving livestock husbandry to reduce lion predation losses and subsequent killing of lions, and studying behavioral adaptations of lions to human activities and persecution. We initially interviewed ranch owners and managers on lion numbers, losses to all mortality factors, husbandry methods, costs, and lion control measures. Studies of husbandry and control methods led to improved livestock management, which gradually reduced losses and retaliatory lion killing. Persecuted lions are secretive and nocturnal, so behavioral research was dependent upon radio collaring, requiring development an effective capture technique. Collars introduced ranchers to their lions as individuals, decreasing their propensity to shoot them after livestock predation. The most important breakthrough was the development of “lion-proof” mobile bomas (corrals) which dramatically reduced night time losses and retaliatory killing. Global positioning system (GPS)-Iridium collars for research into lion movements, allowed development of a Lion Early Warning System to inform ranchers of morning lion locations, allowing them to avoid lions during day time grazing. These measures reduced retaliatory lion killing by 90% between 1998 and 2017. Development of simple and inexpensive hyena-proof bomas for traditional pastoralists dramatically reduced their losses and motivation to poison predators. Studies of lion movements and ecological energetics in relation to human activities have revealed patterns of diel avoidance of humans/livestock by day and predation of wild prey near bomas at night, showing that lions partition their activities temporally in order to utilize high quality hunting habitat while minimizing risk of encountering humans. Studies of predation ecology suggest that lion predation does not have a significant impact on Laikipia’s important population of endangered Grevy’s zebra. Several other carnivore research and conservation projects in Kenya arose out of the initial work in Laikipia.